Clinical Significance of Anti-U1 Ribonucleoprotein Antibody in Anti-Topoisomerase I Antibody-Positive Systemic Sclerosis Patients: A Retrospective Observational Study - Matsuda, Kazuki M; Yoshizaki, Ayumi; Kotani, Hirohito; Kuzumi, Ai; Fukayama, Maiko; Fukasawa, Takemichi; Ebata, Satoshi; Yoshizaki-Ogawa, Asako; Asano, Yoshihide; Oba, Koji; Sato, Shinichi (Archives of Clinical and Biomedical Research, 2021)
Coexistence of anti-topoisomerase (topo) I antibody (Ab) and anti-U1 ribonucleoprotein (RNP) Ab is occasionally observed among patients with systemic sclerosis (SSc). To clarify the clinical significance of anti-U1 RNP Ab in patients with anti-topo I Ab-positive SSc, we conducted a retrospective review of SSc patients initially arrived at our clinic since April 2011 until March 2020. Serum levels of anti-topo I Ab were examined by enzyme-linked immunosorbent assay, and anti-topo I Ab-positive patients were recruited into the study. Serum anti-U1 RNP Ab positivity was explored by chemiluminescent enzyme immunoassay. In total, 92 patients were enrolled into our study. Of these, 11 cases were anti-U1 RNP Ab-positive (anti-U1RNP+) and 81 patients were anti-U1 RNP Ab-negative (anti-U1RNP-). Age of SSc onset was significantly lower in anti-U1RNP+ group than in anti-U1RNP- group (median [25-75th percentiles], 26.8 [20.3-39.6] vs 45.1 [31.5-56.8] years, P < 0.01). Additionally, serum levels of anti-topo I Ab were significantly higher among anti-U1RNP+ patients compared to the others (166 [124-195] vs 135 [104-174] U/mL, P < 0.05). Moreover, concurrence of systemic lupus erythematosus and Sjögren’s syndrome was more common in anti-U1RNP+ group than in anti-U1RNP- group (45.5% vs 1.2%, P < 0.001; 54.5% vs 12.3%, P < 0.01). In conclusion, anti-U1 RNP Ab is associated with early disease onset, reduced vital capacity of the lung, and concurrence of systemic lupus erythematosus and Sjögren’s syndrome among SSc patients with anti-topo I Ab.